2016
DOI: 10.1038/modpathol.2016.117
|View full text |Cite
|
Sign up to set email alerts
|

Harmonized PD-L1 immunohistochemistry for pulmonary squamous-cell and adenocarcinomas

Abstract: Immunohistochemistry of the PD-L1 protein may be predictive for anti-PD-1 and anti-PD-L1 immunotherapy in pulmonary adenocarcinoma and in clinically unselected cohorts of so-called non-small-cell lung cancer. Several PD-L1 immunohistochemistry assays with custom reagents and scoring-criteria are developed in parallel. Biomarker testing and clinical decision making would profit from harmonized PD-L1 diagnostics. To assess interobserver concordance and PD-L1 immunohistochemistry staining patterns, 15 pulmonary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
320
4
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(360 citation statements)
references
References 19 publications
29
320
4
7
Order By: Relevance
“…Another recent study assessed interobserver concordance and PD-L1 IHC staining patterns in 15 pulmonary carcinoma resection specimens using three assays: Dako 28-8, Ventana SP142, and Ventana SP263 (37). Data showed that carcinoma cells could be reproducibly scored, with no differences in interobserver concordance among the tested assays.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study assessed interobserver concordance and PD-L1 IHC staining patterns in 15 pulmonary carcinoma resection specimens using three assays: Dako 28-8, Ventana SP142, and Ventana SP263 (37). Data showed that carcinoma cells could be reproducibly scored, with no differences in interobserver concordance among the tested assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the scoring of immune cells yields low concordance rates and that IHC is probably inadequate for assessment of immune cell expression independent of which assay is selected, with only the possible exception of the SP142 clone, specifically developed for evaluation of tumor associated immune cells (7). Conversely, several studies summarized in Table 1, consistently reported a relatively good agreement for PD-L1 scoring between the pathologists, independent of training and professional education (3,(7)(8)(9)(10).…”
Section: Editorialmentioning
confidence: 99%
“…Similar results were reported recently in a German comparison study, confirming the feasibility of a reproducible PD-L1 tumor cell scoring (28-8 and 22C3 assays yield comparable tumor cell percentages). Despite results are based on 15 cases scored by 9 pathologists, the choice assay may influence percentage of stained tumor cells (more stained with SP263, fewer with SP142) and intensity of stained immune cells (SP263 and SP142 stain more intense) (28).…”
Section: The Pd-l1 Test: Technical Issuesmentioning
confidence: 99%